Beverage consumption in Australian children. Issue 3 (March 2018) - Cockburn, Nicole; Lalloo, Ratilal; Schubert, Lisa; Ford, Pauline J
Abstract Background/objectives While beverages are an important dietary source of water and some essential nutrients, consumption of sweet beverages has increasingly been linked to adverse health outcomes. Currently there is a paucity of longitudinal consumption data on beverage consumption in Australian children. Subjects/methods The Longitudinal Study of Australian Children has run biennially since 2004. Twenty four-hour recall data collected over 6 waves from the birth cohort (aged 0–1 year at baseline) was analysed and demographics were assessed for associations. Results Five thousand one hundred and seven children participated at baseline, with a 71–90% retention of participants at each wave. Water consumption remained consistent with age over time, with more than 90% consuming more than one glass in the last 24-h. Proportions of fruit juice consumers decreased overall. Soft drink and cordial consumer proportions increased from 1% (0–1 year), to 28% (2 years) and 43% (10 years). Between 2 and 10 years, proportions of consumption of full-cream milk decreased by 8% and for skim milk this proportion increased by 51%. High proportions of consumers of soft drink/cordial was significantly associated with older children, males, children with a medical condition, living in a rural area, low socio-economic status and Indigenous Australians. Conclusions Water consumption remained consistently high across the ages, while fruit juice was commonly introduced into the diet early childhood. While proportions of fruit juice consumers decreased after the age of 2 years, proportions of soft drink consumers increased. The findings from this study should assist with surveillance data and inform policy and interventions aimed at reducing consumption of sweet beverages.